Correlation of resistivity value with geotechnical N-Value of sedimentary area in Nusajaya, Johor, Malaysia - Mohd Akip Tan, S. N.; Tonnizam, M. Edy; Saad, R.; Md Dan, M. F.; Nordiana, M. M.; Hazreek, Z. A. M.; Madun, A. (IOP Publishing, 2018)
Electrical resistivity survey and the geotechnical SPT blow counts (N-value) were carried out simultaneously on the tropically weathered sedimentary rock mass for an excavation project at Nusajaya, Johor, Malaysia. This study aims to determine subsurface profile by using 2D-resistivity methods and correlate with N-value derived from boring works. Four boreholes were investigated in five survey lines that revealed the site is underlain by moderately to completely weathered sandstone, clay, silt and shale. Data analysis from 2Dresistivity image shows that zones with high resistivity value generally have high N-value, and vice versa. Five zones have inversed the proportional relation between N-value and resistivity Ωm value due to different types of soil lithology. It indicates that 2D-resistivity is significance to detect bodies of anomalous materials or estimating the depth of bedrock. As a conclusion, the integration of geophysical and geotechnical analysis provides a promise approach to understand some relationship concerning the subsurface subsurface ground through the combination of 2D-resistivity and N-value.